Will AI Enable Organ Regeneration? A Look at the Future of Digital Health - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The quest for functional, lab-grown organs to replace diseased or damaged tissues is one of the most ambitious frontiers in modern medicine. While the field ...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Machine Learning; Medical Ethics